ENVIRONMENTAL MONITORING OF SOILS IN THE AREA ADJACENT TO THE MLYNIV LANDFILL OF RECYCLED RESOURCES - Zelisko , О.; Khirivskyi , П.; Krektun , Б.; Korinets , Ю.; Lopotych , Н.; Mazurak , О.; Verkhola , Г. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The paper investigates the impact of solid household waste stored at the landfill of the Mlynivske municipal enterprise in Rivne region on the soil condition of the adjacent territory. The obtained data on the content of heavy metals indicate a significant anthropogenic impact of the studied object on the ecological state of soils. An increased level of contamination is manifested in the northwestern direction, where the TLV (Threshold Limit Value) for lead and manganese is exceeded by two to three times, for zinc and nickel by one to two times, and by 1.5 times for copper. It is noted that both non-compliance with the technology of solid waste storage and the filtration characteristics of the landfill bottom soils contribute to the formation of leachate. In view of this, it is necessary to prevent leachate from entering aquifers used to provide drinking water to the population. Therefore, at the bottom of the landfill trenches and pits, an artificial base in the form of an impervious surface screen should be arranged, consisting of two layers of 0.2 mm thick soot-stabilized polyethylene film. This will help protect aquifers from contamination. The impervious surface should be laid from the bottom of the pit to a height corresponding to the thickness of one layer of household solid waste (HSW), but not less than 2.25 m (according to DSTU B B.2.1-2-2014) and covered with a protective layer of soil at least 0.5 m thick. To control possible groundwater contamination by the landfill filters, two observation wells are planned. One well should be located upstream of the groundwater flow, and the other downstream. This will allow for ongoing monitoring of the landfill's impact on groundwater and groundwater quality and a comprehensive assessment of the technical condition of this man-made facility.